2019
DOI: 10.1137/17m1148566
|View full text |Cite
|
Sign up to set email alerts
|

Finding Detours is Fixed-Parameter Tractable

Abstract: We consider the following natural "above guarantee" parameterization of the classical Longest Path problem: For given vertices s and t of a graph G, and an integer k, the problem Longest Detour asks for an (s, t)-path in G that is at least k longer than a shortest (s, t)-path. Using insights into structural graph theory, we prove that Longest Detour is fixed-parameter tractable (FPT) on undirected graphs and actually even admits a single-exponential algorithm, that is, one of running time exp(O(k)) · poly(n). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
(57 reference statements)
0
30
0
Order By: Relevance
“…Fomin et al [7] showed that an algorithm for k-(s, t)-Path can be used to solve the Long (s, t)-Path and Long Cycle problems. Bezáková et al [2] showed that an algorithm for k-(s, t)-Path can be used to solve the Exact Detour problem. Using our algorithm for k-(s, t)-Path instead the algorithm of [15] gives faster algorithms for these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Fomin et al [7] showed that an algorithm for k-(s, t)-Path can be used to solve the Long (s, t)-Path and Long Cycle problems. Bezáková et al [2] showed that an algorithm for k-(s, t)-Path can be used to solve the Exact Detour problem. Using our algorithm for k-(s, t)-Path instead the algorithm of [15] gives faster algorithms for these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Similar ideas have successfully been applied to several problems (see e.g. [2,5,10,19,20,32]). Our results also fall in the framework of "above/below" parameterization, with the remark that our parameter of interest is not the value to be optimized but a structural property of the input, which we parameterize near its "critical value".…”
Section: Related Workmentioning
confidence: 96%
“…For each vertex v ∈ S \ R S , we claim that N G (v) ∩ R C = ∅. This follows from the fact that N G (v) = N H (v 1 ) = N H (v 2 ) and Claim 3.5 (5), using that v / ∈ R S implies v 1 , v 2 / ∈ R S . Hence the (up to two) neighbors that v ∈ S \ R S has in C on the Hamiltonian cycle F do not belong to R C , while Claim 3.5 (5) ensures that all vertices of N G (v) are saturated by H and hence belong to C .…”
Section: Claim 34 If There Is a Path Cover Of S In G Having C -Endpmentioning
confidence: 96%
See 1 more Smart Citation
“…From a more general perspective, our work belongs to a popular subfield of Parameterized Complexity concerning parameterization above/below specified guarantees. In addition to [10,7], the parameterized complexity of paths and cycles above some guarantees was studied in [2,16], and [8].…”
Section: Longest Cycle Above Madmentioning
confidence: 99%